Reply to comment on 'Proton beam monitor chamber calibration'. (18th August 2016) - Gomà, Carles; Lorentini, Stefano; Meer, David; Safai, Sairos
Abstract: This reply shows that the discrepancy of about 3% between Faraday cup dosimetry and reference dosimetry using a cylindrical ionization chamber found in Gomà (2014 Phys. Med. Biol. 59 4961 –71 ) seems to be due to an overestimation of the beam quality correction factors tabulated in IAEA TRS-398 for the cylindrical chamber used, rather than to 'unresolved problems with Faraday cup dosimetry', as suggested by Palmans and Vatnitsky (2016 Phys. Med. Biol. 61 6585 –93 ). Furthermore, this work shows that a good agreement between reference dosimetry and Faraday cup dosimetry is possible, provided accurate beam quality correction factors for proton beams are used. The review on W air values presented by Palmans and Vatnitsky is believed to be inaccurate, as it is based on the imprecise assumption of ionization chamber perturbation correction factors in proton beams being equal to unity.